Knowledge and awareness of Human Papillomavirus (HPV) and HPV vaccines among Caribbean youth: the case of the Bahamas - Clemon George; Robin Roberts; Delon Brennen; Lynette Deveaux; Stanley E Read (Taylor & Francis Group, 2020)
There is a high burden of cervical cancer in the Caribbean region, particularly in the Bahamas, yet there are few studies of Human Papillomavirus (HPV) and HPV vaccine in the region. The objective of this study was to assess the knowledge and awareness of HPV and the HPV vaccine among school-aged youth (15-18 years) living in the Bahamas. Cross-sectional data were obtained from the "Getting to Zero" HIV study in the Bahamas conducted in 2014/2015 (n = 1553). The questionnaire elicited information on knowledge of HPV and HPV vaccines, using previously validated scales. Data analysis included Chi-square tests and Mann Whitney U test. In this sample of school-aged youth, only 10.7% (146/1364) had ever heard of HPV. With respect to those who were sexually active (n = 685), only 10.7% had ever heard of HPV. For those who had heard of HPV, knowledge of HPV and HPV vaccines was assessed on an HPV Knowledge and HPV Vaccine Knowledge scale, respectively. There was no statistically significant difference in mean HPV knowledge score between males and females, or HPV vaccine knowledge scores, between males and females. There was a general lack of awareness of HPV and HPV vaccines among school-aged youth in the Bahamas. This is an important gap in the HPV vaccine strategy and cancer prevention, as this is the age at which most people acquire HPV. It emphasizes the importance of developing a careful implementation plan, with an evaluation of knowledge and attitudes, in order to have an effective HPV vaccine uptake.